Validitas LKPD Virtual Field Trip Pencemaran Lingkungan Hidup untuk Melatihkan Keterampilan Literasi Lingkungan Siswa SMA - As-Syauqi, Syarifah Miftahqillah; Rachmadiarti, Fida (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
Environmental pollution is a problem with chain effects has consequences for various aspects of life. One of the contributors to environmental pollution problems is human activity, including production, consumption, and distribution. The consequences of environmental problems that occur require environmental literacy skills as a basic ability that everyone must have to understand that they have a role in solving environmental problems as an effect of every action they take. These abilities need to be trained from an early age through optimizing the role of educational institutions. Through it, the process of forming students basic thinking regarding environmental literacy can be an indicator of achieving quality education goals in line with Sustainable Development Goals (SDGs) point number four. Quality learning that is able to achieve the stated learning objectives needs to be supported by LKPD as teaching materials to make the process more effective. This research aims to produce valid, appropriate virtual field trip LKPD products and describe the validity of their environmental pollution material to develop high school students' environmental literacy. The research method used is research and development (RnD) with a 4D research design. The validation data processed using quantitative descriptive methods. This research produced virtual field trip LKPD with average overall validation score of 4.3 and very valid interpretation, so it can be concluded that the virtual field trip LKPD is valid and suitable for use in learning environmental pollution material to develop high school students' environmental literacy.